P1275 In-hospital outcome of patients with infective endocarditis: is echocardiography enough?. (17th January 2020) - Motoc, A; Kessels, J; Roosens, B; Lacor, P; Van De Veire, N; De Sutter, J; Droogmans, S; Cosyns, B
Abstract: Background: Despite improvements in medical and surgical therapy, infective endocarditis (IE) remains a deadly disease. Echocardiography is the first-line diagnostic tool. However, data regarding its role in the prognostic assessment of in-hospital clinical outcome of IE are scarce. Purpose: We sought to assess the role of echocardiography to predict the in-hospital outcome in a large cohort of patients diagnosed with definite IE and its association with clinical presentation and microorganisms. Methods: We retrospectively included patients from two centers between 2006 and 2018. Transthoracic and transesophageal echocardiography were performed in all patients. The clinical endpoints were in-hospital death, embolic events (cerebrovascular and non-cerebrovascular), shock (septic shock and cardiogenic shock) and cardiac surgery. Results: 183 patients with definite IE (age 68.9 ± 14.2 years old, 68.9% male) were evaluated. Ninety three (50.8%) patients had aortic valve IE and 81 (44.3%) patients presented with mitral valve IE. Twenty three patients had multivalvular IE. The in-hospital mortality rate was 22.4%. Sixty patients (32.8%) had embolic events and 42 (23%) patients developed shock during hospitalization. Surgery was performed in 103 (56.3%) patients. Mitral valve IE on echocardiography was an independent predictor of in-hospital mortality (p = 0.038, OR 0.38, 95% CI 0.15 – 0.94) and aortic valve IE on echocardiography was an independent predictor of embolic events (p = 0.018, OR 0.36, 95% 0.16-0.84). The presence of a new cardiac murmur upon admission was predictive for the need of cardiac surgery (p = 0.042, OR 0.51, 95% CI 0.22- 1.09) and correlated with the severity of valvular regurgitation identified by echocardiography (p = 0.024). Methicillin resistant Staphylococcus aureus (MRSA) as the causative microorganism was an independent predictor for in - hospital mortality and for the development of shock during hospitalization (p = 0.010, OR 0.13 95% CI 0.30 - 0.62 and p = 0.027, OR 6.11, 95% CI 1.22 – 30.37, respectively). No correlation was found between MRSA and echocardiographic parameters. Conclusion: Mitral valve IE was an independent predictor of in - hospital mortality. Furthermore, aortic valve IE was an independent predictor of embolic events. The presence of a new cardiac murmur was predictive for the need of cardiac surgery and correlated with the severity of valvular regurgitation by echocardiography. Our findings suggest that a thorough physical examination upon admission is required in combination with a comprehensive echocardiographic exam for early identification of patients with IE at high - risk for in-hospital death and complications.